Phase Ib Study of Enzalutamide with or Without Sorafenib in Patients with Advanced Hepatocellular Carcinoma. (2nd July 2020) - Harding, James J.; Kelley, Robin K.; Tan, Benjamin; Capanu, Marinela; Do, Gian Kinh; Shia, Jinru; Chou, Joanne F.; Ferrer, Christine S.; Boussayoud, Chayma; Muenkel, Kerri; Yarmohammadi, Hooman; El Dika, Imane; et al.
Abstract: Lessons Learned: Androgen receptor as assessed by immunohistochemistry is expressed in a high proportion of patients with hepatocellular carcinoma (HCC). Enzalutamide at 160 mg orally daily is safe and tolerable in patients with advanced HCC but has no single‐agent antitumor activity. Enzalutamide, a CYP3A4 inducer, at a standard dose of 160 mg reduces the exposure of sorafenib, a CYP3A4 substrate. Enzalutamide and sorafenib is safe and tolerable in patients with advanced HCC, but the addition of enzalutamide to sorafenib did not enhance the antitumor activity of sorafenib. Background: Androgen receptor (AR) interference is deleterious to hepatocellular carcinoma (HCC) in preclinical models. Methods: This is a multicenter, phase Ib study of enzalutamide ± sorafenib in patients with advanced HCC. In part 1, a 3 + 3 dose de‐escalation design with expansion established the recommended phase II dose (RP2D) of enzalutamide in patients in whom sorafenib treatment had failed. In part 2, a 3 + 3 dose escalation with expansion established the safety of enzalutamide with sorafenib in treatment‐naive patients with HCC. Secondary objectives included objective response rate (ORR), progression‐free survival (PFS), overall survival (OS), pharmacokinetics (PK), and determination of AR expression by immunohistochemistry. A 7‐day run‐in with sorafenib alone in part 2 allowed assessment of the impact of enzalutamide on sorafenib pharmacokinetics. Results: In part 1, 16 patients received enzalutamide 160 mg daily. No dose‐limiting toxicity (DLT) occurred; 1 patient required dose reduction. Responses were not observed; median PFS and OS were 1.8 (95% confidence interval [CI]: 1.6–3.6) and 7 (95% CI: 3.6 to not reached [NR]) months, respectively. In part 2, patients received sorafenib 400 mg daily (4) or twice a day (8) both with enzalutamide at the recommended phase II dose—no DLTs were observed. ORR was 10% (95% CI: 0.3–44.5), and median PFS and OS were 2.9 (95% CI: 1.6 to NR) and 6.7 (95% CI: 4.6 to NR) months, respectively. Enzalutamide reduced sorafenib exposure by 60%. Tumor AR expression did not associate with outcome. Conclusion: Enzalutamide is ineffective in HCC; further development is not supported by this study.